Economics and Ethics of Results-Based Financing for Family Planning : Evidence and Policy Implications - Chowdhury, Sadia; Vergeer, Petra; Schmidt, Harald; Barroy, Helene; Bishai, David; Halpern, Scott (World Bank, Washington, DC, 2014)
This paper was developed for World Bank task team leaders (TTLs) and teams designing results-based financing (RBF) programs in family planning (FP). It explores the rationale for introducing such incentives based on insights from classical and behavioral economics, to respond to supply- and demand-side barriers to using FP services. To help the reader understand why incentivizing FP requires specific attention in RBF, the evolution of incentives in vertical FP programs introduced from the 1950s to the early 1990s and the ethical concerns raised in these programs are described. RBF programs after the 1990s were also studied to understand the ways FP is currently incentivized. The paper also touches on the effects of the incentive programs for FP as described in the literature. Finally, it examines ethical concerns related to FP incentives that should be considered during the design, implementation, and evaluation of programs and provides a conceptual framework that can be of use for task teams in the decision making process for FP in RBF programs. It should be noted that the paper is concerned exclusively with developing a framework that can help design ethical programs to address the unmet need for FP.